IADL for identifying cognitive impairment in Chinese older adults: insights from cross-lagged panel network analysis - Xiaotong Zhai; Ruizhe Wang; Ran Liu; Depeng Jiang; Xiaojin Yu (BMC Geriatrics)
Abstract Background As China has entered an aging society, the prevention of cognitive impairment is of great importance. The progression of cognitive impairment is usually a slow and continuous process, with Instrumental Activities of Daily Living (IADL) serving as a sensitive indicator for early prediction of cognitive decline. The objective of this study was to utilize longitudinal network analysis to pinpoint the most sensitive indicators of IADLs to identify cognitive impairment in different populations, and to offer practical recommendations for preventing cognitive impairment among older adults in China. Methods A total of 2,781 participants were selected from the Chinese Longitudinal Healthy Longevity Survey (CLHLS 2014–2018). Cognitive function and IADLs were assessed by Mini-mental State Examination (MMSE) and Chinese modified Lawton scale, respectively. In this study, the cross-lagged panel network (CLPN) model was employed to construct three separate networks for all Chinese older adults, male Chinese older adults, and female Chinese older adults, respectively. Two centrality indices were used to quantify symptom centrality in directed CLPN: In-Expected-Influence (IEI) and Out-Expected-Influence (OEI). Results In the IADLs and cognitive function networks, “Use public transit,” “Make food” and “Walk 1 km” emerged as the most influential and important indicators. The edge “Use public transit → Attention and Calculation” was the strongest edge connection in all three networks. Among older adult males, “General ability” exhibited the most influence on other cognitive domains, followed by “Language,” while “Attention and Calculation” had a weaker influence. Conversely, among older adult females, “Attention and Calculation” was the most influential factor, followed by “General ability” and “Language.” Conclusions This study provides new insights into the associations between specific IADL activities and cognitive function domains among Chinese older adults. Concentrate on monitoring limitations related to “Use public transit,” “Make food” and “Walk 1 km,” and promoting broader life-space mobility may be beneficial to preventing the decline of cognitive function. The findings underscore the importance of targeting interventions not only by specific cognitive domains, but also potentially by gender. Clinical trial number Not applicable.